Female Homosexuality as a Psychiatric Case, or The Story of Confession and Compassion in the Journal Vrach (The Physician, 1898) - Vygovskaia, Natalia (Wiener Slawistischer Almanach, 2023)
The paper analyzes Dr. Rybakov’s article O prevratnykh polovykh oshchushcheniiakh(About Perverse Sexual Sensations) from the widest circulated medical journalVrach (The Physician) in late Imperial Russia. The article, published in two parts insequential issues, presents a hybrid genre of a scientific paper and a patient’s love story.The author uses excerpts from the patient’s diary as evidence to support his argumentabout her neurological disorder. Yet Rybakov’s selections of diary passages turn himinto a plot-maker, who embellishes his scientific investigation with the romanticizedrepresentations of lovesickness, commonly found in literature of the period. Due to theaesthetics of high sensibility, the patient’s identity becomes socially normalized. Yet,the reader can witness the narrator’s conflicted attitude. On the one hand, Rybakovcreates a sympathetic narrative about the patient’s suffering. On the other, the doctorwants to share the successful story of her recovery with the readers. In this article, Iseek to answer the following questions: How does the doctor’s writing differ frompsychiatric texts about female homosexuality of the time and how does the diffusednarrative authority (the presence of two narrators) relate to Rybakov’s scientific argumentation?